Why you can never get to the end of the rainbow and other moments of science - Glass, Don, 1939-; Fentress, Stephen (Bloomington : Indiana University Press, 1993)
Short essays explain such scientific questions as why cats' eyes glow at night, why rivers don't flow in a straight line, and how the world looks to a bee.
"These essays are adapted from scripts for the radio series 'A Moment of science'"--T.p. verso.
Includes bibliographical references.
Keywords: Moment of science (Radio program); Science -- Popular works; Science -- Miscellanea -- Juvenile literature; Science -- Miscellanea